Respostas

2014-07-24T11:53:20-03:00
 \left \{ {{x-3=-y} \atop {3x+2=y+3}} \right.

| x-3 =  - y
| 3x + 2 = y + 3

x - 3 = - y-------------------------vamos isolar o (x)
x = - y + 3-----------substituir o (x)

3x + 2 = y + 3
3x         + 2 = y + 3
3(-y + 3) + 2 = y  3
-3y + 9   + 2 = y + 3 
-3y  + 11      = y + 3  ----------separar os TERMOS
-3y - y = 3 - 11
     -4y = - 8
       y = -8/-4
y = + 8/4
y = 2----------------------------achar o valor de (x)

x = - y + 3

x =  -2 + 3
x = 1

V = {1; 2}

fazendo a verificação (prova real)
para
x = 1
y = 2




x - 3 = - y
1 - 3 = - 2
   -2  = - 2

e

3x + 2 = y + 3
3(1)+2 = 2 + 3
  3  +2 =   5
      5  = 5      correto